Rapid appraisal to improve canal irrigation performance: experience and options - Chambers, Robert; Carruthers, I. (International Irrigation Management Institute, 1986)
Rapid Rural Appraisal (RRA) refers to field evaluation techniques which attempt to optimize cost effectiveness and timely completion of reports. While there is a sizeable literature on RRA techniques in general, little work has been done to apply these techniques to canal irrigation. This paper investigates and reports such applications.